Defining the root cause of reduced H1N1 live attenuated influenza vaccine effectiveness: low viral fitness leads to inter-strain competition - Oliver Dibben (Nature Portfolio, 2021)
Abstract In the 2013–14 and 2015–16 influenza seasons, reduced vaccine effectiveness (VE) was observed for the H1N1 component of the FluMist quadrivalent live attenuated influenza vaccine (QLAIV) in the USA, leading to loss of Advisory Committee on Immunization Practices recommendation. Here we demonstrate in ferrets that 2015–16A/H1N1pdm09 vaccine strain A/Bolivia/559/2013 (A/BOL13) is outcompeted in trivalent (TLAIV) and QLAIV formulations, leading to reduced protection from wild-type challenge. While monovalent (MLAIV) A/BOL13 provided significant protection from wild-type virus shedding and fever at doses as low as 3.0 log10 fluorescent focus units (FFU), it failed to provide a similar level of protection in TLAIV or QLAIV formulation, even at a 6.0 log10 FFU dose. Conversely, clinically effective H1N1 strain A/New Caledonia/20/1999 provided significant protection in MLAIV, TLAIV, and QLAIV formulations. In conclusion, reduced A/BOL13 replicative fitness rendered it susceptible to inter-strain competition in QLAIV, contributing to its reduced VE in the 2015–16 season.